Hsp70 associates with Rictor and is required for mTORC2 formation and activity - Martin, Jheralyn (2008)
mTORC2 is a multiprotein kinase composed of mTOR, mLST8, PRR5, mSIN1 and Rictor. The complex is insensitive to rapamycin and has demonstrated functions controlling cell growth, motility, invasion and cytoskeletal assembly. mTORC2 is the major hydrophobic domain kinase which renders Akt fully active via phosphorylation on serine 473. We isolated Hsp70 as a putative Rictor interacting protein in a yeast two-hybrid assay and confirmed this interaction via co-immunoprecipitation and colocalization experiments. In cells expressing an antisense RNA targeting Hsp70, mTORC2 formation and activity were impaired. Moreover, in cells lacking Hsp70 expression, mTORC2 activity was inhibited following heat shock while controls demonstrated increased mTORC2 activity. These differential effects on mTORC2 activity were specific, in that mTORC1 did not demonstrate Hsp70-dependent alterations under these conditions. These data suggest that Hsp70 is a component of mTORC2 and is required for proper assembly and activity of the kinase both constitutively and following heat shock.